A liberdade em Polanyi - Baptista, António (The concept of freedom in Polanyi., 2018)
Karl Polanyi's The Great Transformation is a powerful criticism of free market ideology and its intrinsic assumptions that is based on an implicit political theory of freedom. The attempt is made here of reconstructing and making explicit Polanyi's concept of "freedom in a complex society" in light of his commitment to a sui generis form of socialism and his lifelong opposition to arguments as found typically in Friedrich Hayek's The Road to Serfdom. (English)
Keywords: Hayek, Friedrich A. von (Friedrich August), 1899-1992; POLANYI, Karl, 1886-1964; Road to Serfdom (book); degrees of freedom; democracia; democracy; freedom; freedom in a complex society; liberdade; planificação; planning; socialism; socialismo; transformative learning

Desenvolvimento territorial no Brasil: uma análise a partir da concepção teórica de Karl Polanyi - Waldecy Rodrigues; Nayara Silva Santos (Desarrollo territorial en Brasil: un análisis desde Karl Polanyi., 2018)
This paper analyzes the municipal development in Brazil from the theoretical design of Karl Polanyi. Methodologically, the Polanyi's city development index of Polanyi (IDMP). The results show that according to the concepts analyzed, the Brazilian municipalities, in their majority, have multidimensional incipient features and that there is a direct positive relationship between economic pluralism and quality of life levels. (English)
Keywords: Brazil; abordagem multidimensional; approche multídimensionnelle; city development; desarrollo; desarrollo municipal; desenvolvimento; desenvolvimento municipal; development; developpement; developpement des municipalites; economia plural; economía diversa; enfoque multidimensional; multidimensional approach; plural economy; économie plurielle